PENGARUH RETURN ON ASSETS (ROA), RETURN ON EQUITY(ROE), NET INTEREST MARGIN (NIM) DAN RASIO BIAYA OPERASIONAL PENDAPATAN OPERASIONAL (BOPO), TERHADAP HARGA SAHAM BANK DI BURSA EFEK INDONESIA. - Rachmawati, Titiek (DiE: Jurnal Ilmu Ekonomi dan Manajemen, 2009)
The purpose of this research is to know the ROA (Return On Assets), ROE (Return On Equity), NIM (Net Interest Margin) and BOPO ratios that influence simultaneously or partially to the shares price in Indonesia Stock Exchange.The research is causal comparative the data resource that were used from bank aunual report 2003 until 2008 from Indonesia Stock exchange . According to the criteria in this research, the samples are 10 banks in industrial banking. For analysing the model and testing the research hypotheses, we used multiple linear regression analysis statistic method.             Based on the research result and the hypotheses test, we can conclude as follow : 1)   ROA, ROE, NIM and BOPO ratios influence simultaneausly to the shares price. 2)   ROA, ROE, and BOPO ratios influence partially to the shares price while NIM ratio had proved not influence. Key words : ROA (Return On Assets), ROE ( Return On Equity), NIM ( Net                     Interest Margin), BOPO ratio, shares price.